THE DEVELOPMENT OF THE PHENOMENA OF ISLAMIC MARKETING, ISLAMIC BRANDING, AND INDONESIAN MUSLIM MIDDLE CLASS - Nugraha, Yudha Dwi (Academy of Education Journal, 2023)
Islam as a religion has been found to impact the ethical beliefs and behaviours of Muslim consumers from different countries, as well as consumers’ choice of services and some taboo products on the basis of Islamic Shariah law. The emergence of Islamic marketing and Islamic branding in various parts of the world and the increasing middle-class Muslims in Indonesia are interesting phenomena to study. Using the qualitative approach, this study aims to explore the development of Islamic marketing, Islamic branding, and middle-class Muslim in Indonesia. The results showed that Islamic marketing is still new in the literature and the definition of the true meaning of Islamic marketing is still being developed. In addition, Islamic branding is closely related to the halal concept. The behaviour of Muslim middle-class in Indonesia is very challenging and it has enormous potential. The discussions are explained further.